2012
DOI: 10.5352/jls.2012.22.1.49
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Genistein on Cell Proliferation and Adipogenesis in Mouse 3T3-L1 Preadipocytes

Abstract: The effects of genistein on cell proliferation and adipogenesis were examined in mouse 3T3-L1 preadipocyte cells. Genistein decreased viability of 3T3-L1 pre-adipocytes in a dose-dependent manner. Oil Red O staining of these cells also indicated that adipogenesis was inhibited by 50 μM genistein treatment. We investigated the molecular mechanisms involved in the decrease in cell viability in genistein-treated 3T3-L1 cells by conducting an oligo DNA microarray analysis. We selected the sirtuin-1 gene, one of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
1
0
1
Order By: Relevance
“…According to a recent research, the intake of isoflavone after menopause could increase the amount of calcium in bones of women and prevent osteoporosis [15]. It has been reported that isoflavone can decrease the process of adipogenesis in mouse cells [16]. In addition, the intake of isoflavone can result in improved blood lipid with antioxidant effect in mouse fed with a high cholesterol diet [17].…”
Section: Introductionmentioning
confidence: 99%
“…According to a recent research, the intake of isoflavone after menopause could increase the amount of calcium in bones of women and prevent osteoporosis [15]. It has been reported that isoflavone can decrease the process of adipogenesis in mouse cells [16]. In addition, the intake of isoflavone can result in improved blood lipid with antioxidant effect in mouse fed with a high cholesterol diet [17].…”
Section: Introductionmentioning
confidence: 99%
“…최근 들어 평균수명이 크게 증가하면서 삶의 질에 대한 인식의 변화로 인하여 운동요법이 나 식이요법들이 각광받고 있으며, 이외에도 체중 조절에 효과적인 기능성 원료, 특히 식물성 화합물인 파이토케이칼 (phytochemical)을 이용한 항 비만 활성 검증과 그 작용 기전을 이해하고자 하는 연구들이 계속되고 있다 (Kang et al, 2007;Kang et al, 2008;Mercader et al, 2011;Perez-Vizcaino et al, 2006;Rayalam et al, 2008). 이러한 파이토케 이칼은 과일이나 야채 같은 과채류 등에 많이 포함되어 있으며 비영양 성분들로 항산화, 항염, 항암 등의 생리활성에 효능이 있다고 알려져 있고, 항비만과 관련하여 지방세포의 세포주기를 조절하여 관련 단백질 및 유전자의 발현을 조 절하는 것으로 보고되고 있다 (Eberhardt et al, 2005;Khor et al, 2008;Lim et al, 2012). 담자균류(Basidiomycota)의 민주금버섯목(Aphyllophorales), 소나무비늘버섯과(Hymenochaetaceae), 시루뻔버 섯속(Inonotus)에 속하는 차가버섯(Inonotus obliquus (Pers.)…”
unclassified